PENGEMBANGAN MODUL PENGAJARAN BAHASA INGGRIS UNTUK PROGRAM STUDI EKONOMI SYARIAH BERBASIS CONTEXTUAL TEACHING LEARNING (CTL) - M. Arif Rahman Hakim; Yuda Septian Kurniawan; Andri Saputra (STIESNU Bengkulu, 2019)
Abstract Based on the results of a preliminary study conducted by researchers in the Sharia economics study program of Sharia Economics Studies College of Nahdlatul Ulama (STIESNU) Bengkulu, the lecturer and students still have problems in the teaching and learning process in English subject. The main problem that they often face is that they still felt difficult to find the teaching materials based on expectations of the lecturer and students. So based on the results of the analysis of the researchers, they have to apply a development research to solve the problems. The results of this study is a modul as the teaching materials for English subject based on the principles of English for Specific Purposes (ESP) and with the Contextual Teaching and Learning (CTL) approach which developed by using the ASSURE model that followed the stages of analyze learners; state objectives; select, modify media, or design materials; utilize technology, media, and materials; requires learner participation, and, evaluate and revise. In addition, at the final stage, this teaching material product also validated by two experts. Keywords: Teaching Module, Islamic Economics, ESP, CTL) Abstrak Berdasarkan hasil studi awal yang dilakukan oleh para peneliti di program studi ekonomi syari’ah Sekolah Tinggi Ilmu Ekonomi Syari’ah Nahdlatul Ulama (STIESNU) Bengkulu, dosen pengajar dan para mahasiswa masih memiiki permasalahan dalam proses belajar mengajar dimata kuliah Bahasa Inggris. Problem utama yang seringkali mereka hadapi adalah mereka masih merasa kesulitan dalam menemukan bahan ajar yang sesuai ekpektasi dosen pengajar dan para mahasiswanya. Sehingga berdasarkan hasil analisis para peneliti, untuk memecahkan permasalahan yang ada perlu dilakukan penelitian pengembangan. Hasil dari penelitian ini adalah produk bahan ajar mata kuliah Bahasa Inggris berbentuk modul bersasarkan prinsip English for Specific Purposes (ESP) dan dengan pendekatan Contextual Teaching and Learning (CTL) yang dikembangkan menggunakan model ASSURE yang telah melalui tahapan analisis pembelajaran; penentuan standar dan tujuan; pemilihan strategi, teknologi, media dan bahan ajar; mengikut sertakan partisipasi peserta didik dan evaluasi. Selain itu pada tahap akhir, produk bahan ajar ini juga telah melewati tahap validasi dari dua orang ahli Kata Kunci: Modul Pengajaran, Ekonomi Syari’ah, ESP, CTL